2009
DOI: 10.1017/s095927090900817x
|View full text |Cite
|
Sign up to set email alerts
|

Surveys, distribution and current status of the Madagascar Harrier Circus macrosceles in Madagascar

Abstract: We conducted a 16-month country-wide survey to determine the status of the threatened Madagascar (Marsh) Harrier Circus macrosceles from 2005 to 2006. We searched for harriers in varying habitat types, focusing on marshes, grasslands and savannas, secondary forests and the edge of primary forests. We surveyed 68% of the districts of Madagascar which contain 71% of the potential harrier habitat throughout the country. We recorded 80 individuals of this sexually dimorphic raptor; 48 males and 32 females of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Circus macrosceles A. Newton, 1863 -This globally Vulnerable (IUCN 2011) endemic to the Madagascar region has an estimated global population size of 250-500 pairs, restricted in Madagascar to marshes and grassland in the centre and north-west of the island (René de Roland et al 2009). We observed a pair in courtship -pair-formation flights as described by René de Roland et al (2004) -during August 2010 and September 2011, but breeding was not confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Circus macrosceles A. Newton, 1863 -This globally Vulnerable (IUCN 2011) endemic to the Madagascar region has an estimated global population size of 250-500 pairs, restricted in Madagascar to marshes and grassland in the centre and north-west of the island (René de Roland et al 2009). We observed a pair in courtship -pair-formation flights as described by René de Roland et al (2004) -during August 2010 and September 2011, but breeding was not confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Population density and distribution should be taken into account when developing conservation and management plans for species (Lopes et al, 2008;de Roland et al, 2009;Mattos et al, 2009). In this regard, some hotspot areas for Krüper's Nuthatch should be identified for conservation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Three harrier taxa (C. m. macrosceles, C. m. maillardi and C. maurus) are currently listed as either Vulnerable or Endangered (IUCN Red List 2014), while a fourth (C. macrourus) is listed as near threatened due to steep population declines (BirdLife International, 2004). In Madagascar and Reunion, habitat transformation and human disturbance are listed as one of the main threats to C. m. macrosceles (De Roland et al, 2009) and C. m. maillardi (Bretagnolle et al, 2000). The southern African endemic C. maurus is estimated to have fewer than 1000 mature individuals (Curtis et al, 2004), and in addition, their primary nesting habitat is threatened by agriculture (Curtis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%